Evaluation of Clinical, Morphological and Pathohistological Characteristics of Thymomas - Our Ten Year Experience - Lovrenski, Aleksandra; Tegeltija, Dragana; Jeličić, Ivana; Bijelović, Milorad; Đurić, Dejan; Panjković, Milana (Archive of Oncology, 2018)
Background: Thymomas are rare neoplasms arising from tissue elements of the thymus. The objective of the study was to analyse clinical characteristics of patients with thymoma, as well as morphological and patohistological features of neoplasms.Methods: Retrospectively we studied 41 medical records and patohistological material of patients reffered to the Institute of  pulmonary diseases of Vojvodina between the January of 2005 and December of 2014.Results: Patient age at presentation ranged from 19 to 77 years. A slight female preponderance was detected, with 24 (58,5%) females and 17 (41,5%) males being affected. All types of thymoma more often occured in males, accept subtype B1. Patients with type A thymoma and subtype B1 were mainly asymptomatic, while patients with subtype B2 and type AB presented with dyspnea, dysphagia, pain and cough. Myasthenia gravis often was associated with type A (40%). The most common histologic type was subtype B1. 23 (56%) patients had a tumor diameter between 5 and 10 cm. Five patients had malignant thymoma, and the most common types of thymoma that showed signs of capsula invasion or pleural and pericardial implants were type AB (60%) and subtype B2 (50%). Biopsies of suspected tissue were obtained through a sternotomy, video-assisted thoracoscopy surgery, and video-assisted mini thoracotomy, and after setting a diagnosis on ex tempore analysis, the lesions were removed by thymectomy or extirpation of the tumor mass.Conclusion: Thymomas have variable clinical presentations. Clinical outcome correlates with histological type, size and clinical stage, as well as the ability to achieve complete tumor resection.
Keywords: Thymoma; Neoplasms